Cyclist test on particleboards and utilization of their liquid disposal for fertilizer. Issue 1 (March 2021) - Nuryawan, A; Siringo-Ringo, F J; Nasution, T I; Banurea, R; Hartini, K S; Elfiati, D
Abstract: Cyclist test on particleboards (PBs) bonded urea-formaldehyde (UF) resin was intended to be carried out in order to predict their degradation thus recycling of these products was possible. In this contribution, PBs bonded by five types of UF resins namely 0.95; 1.05; 1.15; 2.00; and commercial were examined using cyclist test. The test consists of cycles of five treatment steps, i.e., measurement of initial thickness dimension, immersion in water at ambient temperature for 24 h, measurement of swelling thickness dimension, drying in convection oven at (103 + 2)°C for 24 h, and measurement of oven-dry thickness dimension. This cycle was applied until the specimens were not possible to be measured their thickness because of broken-down of the PBs. Further, water disposal in this experiment, then was utilized as fertilizer to Swietenia mahagoni seedlings. Observation on growth parameters (stem height and diameter) and biomass parameters (dry weight of top and root) of the seedlings were conducted for 12 weeks after planted. Result of this study showed PBs bonded by low mole of UF resins (0.95; 1.05 and 1.15) have had faster degradation compare to those of 2.00 and commercial one. Both growth and biomass parameters of the seedlings increased but statistically not different among the samples. These findings suggested that PBs bonded UF resins can be recycled using water-soaking process and the liquid disposal of this activity can be utilized as fertilizer.